Clinical manifestations of chronic atrophic gastritis - Rodriguez-Castro, Kryssia Isabel; Franceschi, Marilisa; Noto, Antonino; Miraglia, Chiara; Nouvenne, Antonio; Leandro, Gioacchino; Meschi, Tiziana; de' Angelis, Gian Luigi; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Although the actual prevalence of chronic atrophic gastritis is unknown and it is probable that this entity goes largely underdiagnosed, patients in whom diagnosis is established usually present advanced stages of disease. Destruction of parietal cells, either autoimmune-driven or as a consequence of Helicobacter pylori infection, determines reduction or abolition of acid secretion. Hypo/achloridia causes an increase in serum gastrin levels, with an increased risk of the development of neuroendocrine tumors. Microcytic, hypochromic anemia frequently precedes the development of megaloblastic, vitamin B12-associated anemia. Moreover, vitamin B12 deficiency,may cause elevation of homocysteine, with an increase in the cardiovascular risk, and may be associated with neurological manifestations, mainly characterized by spinal cord demyelination and atrophy, with ensuing sensory-motor abnormalities. Gastrointestinal manifestations seem to be associated with non-acid reflux and tend to be non-specific.